2014
DOI: 10.1210/jc.2014-2295
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Copeptin and Vasopressin in a Population From the Community and in People With Chronic Kidney Disease

Abstract: This study in a normal population, the largest ever with measurements of both peptides, shows that copeptin and vasopressin concentrations correlated well. But their relationship is distorted in CKD, suggesting that the peptide clearances differ when the renal function is impaired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 29 publications
9
119
0
Order By: Relevance
“…UD (or specific gravity) may be evaluated in 7 colored grades with commercially available dipsticks (Labtix 8SG and Multistix 8SG AMES/Bayer Diagnostics) or evaluated by refractometry using a hand-held refractometer (Pen Urine S.G., Atago, Tokyo, Japan) [45]. In the DESIR study (a cohort of the French population), UD was measured with dipsticks in fresh spot morning urine samples from 1,604 subjects, and eU osm was calculated (same formula as here) [8]. Median (IQR) eU osm was 664 (272) mosm/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UD (or specific gravity) may be evaluated in 7 colored grades with commercially available dipsticks (Labtix 8SG and Multistix 8SG AMES/Bayer Diagnostics) or evaluated by refractometry using a hand-held refractometer (Pen Urine S.G., Atago, Tokyo, Japan) [45]. In the DESIR study (a cohort of the French population), UD was measured with dipsticks in fresh spot morning urine samples from 1,604 subjects, and eU osm was calculated (same formula as here) [8]. Median (IQR) eU osm was 664 (272) mosm/L.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of non-peptide, orally active selective AVP receptor antagonists (vaptans) [5,6] and of a reliable ELISA for the measurement of copeptin, a validated surrogate of AVP [7,8], has opened the door for a number of studies addressing the AVP/thirst pathway and osmoregulation in general (see review in [9]).…”
Section: Introductionmentioning
confidence: 99%
“…43 It is of interest that fructose, but not glucose, stimulates vasopressin release in humans. 44,45 We recently showed that orally administered fructose augments circulating vasopressin levels (as determined by measuring copeptin, a validated biomarker for vasopressin 46 ) and urinary concentration in dehydrated rats. 47 Fructose also stimulates urinary sodium reabsorption 48 and reduces urea excretion 49 similar to vasopressin.…”
Section: Vasopressin: the Survival Hormonementioning
confidence: 99%
“…An estimated urine osmolarity (eU osm ) was calculated by an equation based on the sum of the three major urinary solutes making up 90-95% of the urinary osmoles [13]. …”
Section: Methodsmentioning
confidence: 99%